TRADISI MESEMBEQ DALAM PELAKSANAAN RITUAL PADA UMAT HINDU DI KOTA MATARAM - Arsana, I Komang Budi (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
This study aims to conduct a study of the mesembek tradition carried out by Hindus in Mataram City. This research was designed in descriptive qualitative research by focusing on case studies. Based on the results of the study it was found that the background of the mesembeq tradition to Hindus in the city of Mataram was to enhance sradha (belief, faith) and bhakti (worship, respect) as cultural preservation. The function of the mesembeq tradition in Hindus in the city of Mataram, which has a religious function and serves as a defense of the identity of Hindus in the city of Mataram. The meaning of the mesembeq tradition in Hindus in the city of Mataram, which is meaningful to develop the traits that are Brahma, Wisnu and Iswara / Siwa. Lord Brahma, which is the manifestation of Ida Sang Hyang Widhi Wasa / God Almighty as the creator, symbolized in red colour, in sembeq, red is found in betel nuts, this symbol means that people who use sembeq have the creativity and creation in their lives, can create good and positive things for the life of mankind and the universe. The ingredients of betel leaves, according to the color are symbolized by dark colors, in the spider, the symbol of Lord Vishnu. The nature of Dewa Vishnu that needs to be manned by mankind is nurturing. People who use sembeq are expected to have a sense of love and affection for all beings, such as Lord Vishnu guarding the existence of the universe. Chalk is used as an ingredient for making sembeq, white is a symbol of Iswara / Siwa deity. The use of lime in making edible food so that its users are active in innovating, have the initiative to make a life change towards a better direction, always carry out the truth, make changes towards better.